PERENCANAAN GEDUNG PAVILIUN GARUDA II RUMAH SAKIT DOKTER KARIADI SEMARANG - Bernard Bayu Baskoro; Daniel Erlanda; Nuroji Nuroji; Purwanto Purwanto (Jurnal Karya Teknik Sipil, 2013)
Design of Paviliun Garuda II  dr. Kariadi Hospital Building, Semarang is designed using the Special Moment Frame System (SMFS). With the election of SMFS system expected to behave ductile structure, because ductile structure not only has large energy but also has a large caapacity in the resist earthquake loads. In system of SMFS, we have to use the concept of strong column weak beam in which the vertical elements of the structure (column) must be made stronger than the horizontal elements of the structure (beam), so that the plastic joints formed first on the beam. In addiction, beam-column joint must also be properly designed to prevent the collapse first. The technique of design and analysis structure, by using the SAP 2000v14 program, will obtain internal forces used to calculate the number of the reinforcements needed by the structure. It is in accordance with Indonesian National Standard or SNI as the main guidance in design of Paviliun Garuda II  dr. Kariadi Hospital Building, Semarang.